Depresión y su influencia en el desarrollo social de una niña de 8 años con padres separados, en la Junta Cantonal de Protección de Derechos de Babahoyo - Romero Vergara, Génesis Dejaneira (2021)
Depression is feeling sad or discouraged at some moments in life, however, it should be noted that depression in children sometimes feel sad or without interest in doing the things they used to do before, symptoms of sadness or crying predominate. The present case study, a prerequisite for obtaining the title of Clinical Psychologist in a complex examination modality, whose line of research is psychological counseling whose subject is depression and its influence on the social development of an eight-year-old girl with parents separated, in the cantonal board of protection of rights of Babahoyo. Its general objective is to determine how separation from her parents causes depression and affects social development in an eight-year-old girl, the signs and symptoms of the problem were evaluated through psychological techniques such as the psychological interview as a questionnaire test of Infant depression, Hamilton anxiety scale test, projective tests such as PHT detecting findings in the emotional, cognitive, social and somatic areas, facilitating the framing of the presumptive diagnosis Separation anxiety disorder and also the execution of the therapeutic scheme with a cognitive approach behavioral.